Pengendalian Persediaan Bahan Baku Kedelai Berbasis EOQ pada Industri Tempe dengan Karakteristik Rantai Pasok Wilayah Kepulauan - Jusak Ubjaan; Christi Natali Wattimena; Paulina Wokanubun (Univiversitas Dr. Djar Wattiheluw, 2026)
The tempe industry relies heavily on soybean availability as the primary raw material; however, supply uncertainty and fluctuations in the supply chain may disrupt production continuity. Ineffective inventory management can increase operational costs and create risks of raw material shortages. This study aims to analyze soybean inventory control at Rumah Tempe Asli HB & Azaki Ambon using the Economic Order Quantity (EOQ) approach. This research employed a descriptive quantitative method, with data collected through observation, interviews, and documentation. Data analysis was conducted by calculating the optimal order quantity, ordering frequency, safety stock, reorder point, and Total Inventory Cost. The findings indicate that the company’s existing inventory management system has not been optimal because purchasing decisions are still based on operational needs rather than quantitative inventory planning. The implementation of the EOQ method provides a more efficient inventory control strategy by optimizing order quantities, reducing ordering frequency, and improving inventory cost management compared to the company’s current practice. Furthermore, determining safety stock and reorder point enables the company to anticipate supply disruptions and maintain production continuity. This study contributes practical insights for improving inventory management strategies among food-based micro and small enterprises, particularly those operating in island regions with supply chain challenges.